Social and demographic factors contributing to the spread of multiple drug resistant tuberculosis in the Russian Federation: a systematic review - I. A. Bykov (Туберкулез и болезни лёгких, 2022)
The objective: to identify and systematize social and demographic risk factors for the development and spread of multiple drug resistant tuberculosis (MDR TB) in the Russian Federation (RF) by means of a systematic review of existing publications.Subjects and Methods. A systematic literature review was performed in accordance with the PRISMA criteria and included studies conducted in the Russian Federation from 2011 to 2021. Out of 2,861 publications, 26 studies were selected and analyzed.Results. According to the reviewed studies, patients with a history of incarceration, low income, unemployed, homeless, and patients suﬀering from alcohol and nicotine addiction are more susceptible to MDR TB. It was also found that MDR TB most often aﬀected people of working age with a clear trend towards a younger cohort. The inﬂuence of such factors as gender and location on MDR TB risk is not clear due to conﬂicting data and comparative strength of evidence in publications.